'I am two distinct beings': Paul de Man's authenticating project. Issue 2 (3rd April 2017) - Jones-Katz, Gregory
Abstract: Belgian-American critic Paul de Man's postwar relationship to his wartime past has been fiercely debated since the 1987 discovery of almost 200 pro-German articles that he wrote in his youth during the Nazi occupation of his native Belgium. What were the reasons for his postwar silence over this and how did this relationship shape his deconstructionist writings? Here, it is argued that after his 1948 emigration to America, de Man, with single-minded, almost obsessional, determination pursued an authenticating project, the goal of which was to become an author who never (again) committed the mistakes of his youth. To realize his goal, de Man underwent a decades-long spiritual conversion that can be viewed as embodying the tension between two models of conversion in Western culture: metanoia – the transformation of one's way of thinking and being – and epistrophē – the return to the source of one's way of thinking and being. While de Man's conversion at first entailed the straightforward renunciation of and silence about his wartime life, his repudiation eventually fashioned an opposition between his present and past. This opposition remained 'undeconstructed' – his collaborationist identity became an unrepresented presence, 'a stowaway' that endured and in great part defined him. Evidence of the tension between de Man's opposed aims – his divided conversion – is perhaps most legible in his postwar writings.